Novel Glycopolymer Eradicates Antibiotic- and CCCP-Induced Persister Cells in Pseudomonas aeruginosa - Narayanaswamy, Vidya P.; Keagy, Laura L.; Duris, Kathryn; Wiesmann, William; Loughran, Allister J.; Townsend, Stacy M.; Baker, Shenda (Frontiers in Microbiology, 2018)
Antibiotic treatments often fail to completely eradicate a bacterial infection, leaving behind an antibiotic-tolerant subpopulation of intact bacterial cells called persisters. Persisters are considered a major cause for treatment failure and are thought to greatly contribute to the recalcitrance of chronic infections. Pseudomonas aeruginosa infections are commonly associated with elevated levels of drug-tolerant persister cells, posing a serious threat to human health. This study represents the first time a novel large molecule polycationic glycopolymer, poly N-acetyl, arginyl glucosamine (PAAG), has been evaluated against antibiotic and carbonyl cyanide m-chlorophenylhydrazone (CCCP) induced P. aeruginosa persisters. PAAG eliminated persisters at concentrations that show no significant cytotoxicity on human lung epithelial cells. PAAG demonstrated rapid bactericidal activity against both forms of induced P. aeruginosa persister cells resulting in complete eradication of the in vitro persister cells within 24 hours of treatment. PAAG demonstrated greater efficacy against persisters in vitro than antibiotics currently being used to treat persistent chronic infections such as tobramycin, colistin, azithromycin, aztreonam and clarithromycin. PAAG caused rapid permeabilization of the cell membrane and caused significant membrane depolarization in persister cells. PAAG efficacy against these bacterial subpopulations suggest it may have substantial therapeutic potential for eliminating recurrent P. aeruginosa infections.